2020
DOI: 10.1093/jac/dkz532
|View full text |Cite
|
Sign up to set email alerts
|

Metallo-β-lactamase resistance in Enterobacteriaceae is an artefact of currently utilized antimicrobial susceptibility testing methods

Abstract: Background MBLs are a major contributor to β-lactam resistance when tested using CAMHB. Despite in vitro resistance, positive outcomes have been reported in MBL-infected patients following carbapenem treatment. The impact of physiological zinc concentrations on this in vitro–in vivo MBL discordance warrants investigation. Objectives To evaluate meropenem in vitro activity against MBL-producing Enterobacteriaceae in zinc-deple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 43 publications
0
42
0
Order By: Relevance
“…MBL enzymes can readily hydrolyze carbapenems in vitro, yet some data suggests that their ability to cause carbapenem resistance is an artifact of the current testing modalities that utilize media with supraphysiologic zinc concentrations. 93 Since zinc is required at the active site of the enzyme, the quantity of zinc at the site of infection could impact the function of the enzyme and also the rate of antibiotic hydrolysis. However, the data are inconclusive.…”
Section: Carbapenemsmentioning
confidence: 99%
See 1 more Smart Citation
“…MBL enzymes can readily hydrolyze carbapenems in vitro, yet some data suggests that their ability to cause carbapenem resistance is an artifact of the current testing modalities that utilize media with supraphysiologic zinc concentrations. 93 Since zinc is required at the active site of the enzyme, the quantity of zinc at the site of infection could impact the function of the enzyme and also the rate of antibiotic hydrolysis. However, the data are inconclusive.…”
Section: Carbapenemsmentioning
confidence: 99%
“…Asempa et al found that meropenem against a panel of NDM-, VIM-, and IMP-producing Enterobacterales appeared resistant in vitro but generated >1 log bacterial killing in murine infection models. 93 They showed that the meropenem in vivo activity better correlated with MICs performed in zinc-depleted media, where the isolates appeared susceptible to carbapenems, than in traditional cation adjusted Mueller Hinton broth.…”
Section: Carbapenemsmentioning
confidence: 99%
“…However, these organisms are susceptible to carbapenems in vivo, where nutritional immunity restricts zinc concentrations to much lower levels. Removal of zinc from MHB broth more reliably predicts in vivo activity of carbapenems against these organisms [ 16 ]. Rigid continuation of AST paradigms utilizing only standard bacteriological media overlooks potential useful activities of the currently available antibiotics against multidrug-resistant bacteria [ 14 ], but it also hinders the transition of pharmacodynamic analysis of innate immunity synergy with antibiotics to a more clinical mainstream.…”
Section: Conventional Bacteriologic Media: An Obstacle To Our Completmentioning
confidence: 99%
“…The purpose of this study is to evaluate the efficacy of cefiderocol under simulated human plasma concentrations over 24 h against clinical strains with a cefiderocol MIC around the breakpoint in a one-compartment in vitro chemostat model. MBL-producing strains were also included in this study because of the limited treatment options for such bacteria, and difficulties in evaluation by animal models have been reported due to the in vitro-in vivo discordance against MBL producers caused by the poor activity of MBL in animal models ( 7 ). Overall, this chemostat model is expected to provide useful information for treatment against isolates with cefiderocol MICs of 0.5 to 4 μg/ml, including MBL producers.…”
Section: Textmentioning
confidence: 99%